2021
DOI: 10.3390/nu13020342
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin as a Promising Molecule for the Treatment of Post-Ischemic Brain Neurodegeneration

Abstract: The available drug therapy for post-ischemic neurodegeneration of the brain is symptomatic. This review provides an evaluation of possible dietary therapy for post-ischemic neurodegeneration with myricetin. The purpose of this review was to provide a comprehensive overview of what scientists have done regarding the benefits of myricetin in post-ischemic neurodegeneration. The data in this article contribute to a better understanding of the potential benefits of myricetin in the treatment of post-ischemic brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 145 publications
(158 reference statements)
0
25
0
Order By: Relevance
“…The discrepancy of myricetin between its low oral bioavailability and neuroprotective effects could be coordinated by a metabolism hypothesis: the orally administered myricetin could be converted into a metabolite that penetrates the blood-brain-barrier. Mechanistic studies have revealed that inhibition of neuroinflammation, oxidative stress, and cellular apoptosis ( Jang et al, 2020 ; Boriero et al, 2021 ; Deng et al, 2021 ; Hamdi et al, 2021 ; Pluta et al, 2021 ), activation of nuclear factor E2-related factor 2 ( Nrf2 ) ( Wu et al, 2016 ), extracellular signal-regulated kinase 1/2 (ERK1/2) ( Lei et al, 2012 ; Jang et al, 2020 ), protein kinase B (Akt) ( Sun et al, 2018 ), and cyclic adenosine monophosphate-response element binding protein (CREB) ( Lei et al, 2012 ), inhibition of intracellular Ca 2+ increase ( Oyama et al, 1994 ; Chang et al, 2015 ), and inhibition of c-Jun N-terminal kinase (JNK) ( Jang et al, 2020 ) or p38 ( Hagenacker et al, 2010 ; Sun et al, 2018 ; Jang et al, 2020 ) may mediate the neuroprotective actions of myricetin. On the basis of these reports, we conclude that myricetin, dependent on its metabolites which possess neuroprotective activities, could be developed as a potential candidate for the treatment of nervous system disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy of myricetin between its low oral bioavailability and neuroprotective effects could be coordinated by a metabolism hypothesis: the orally administered myricetin could be converted into a metabolite that penetrates the blood-brain-barrier. Mechanistic studies have revealed that inhibition of neuroinflammation, oxidative stress, and cellular apoptosis ( Jang et al, 2020 ; Boriero et al, 2021 ; Deng et al, 2021 ; Hamdi et al, 2021 ; Pluta et al, 2021 ), activation of nuclear factor E2-related factor 2 ( Nrf2 ) ( Wu et al, 2016 ), extracellular signal-regulated kinase 1/2 (ERK1/2) ( Lei et al, 2012 ; Jang et al, 2020 ), protein kinase B (Akt) ( Sun et al, 2018 ), and cyclic adenosine monophosphate-response element binding protein (CREB) ( Lei et al, 2012 ), inhibition of intracellular Ca 2+ increase ( Oyama et al, 1994 ; Chang et al, 2015 ), and inhibition of c-Jun N-terminal kinase (JNK) ( Jang et al, 2020 ) or p38 ( Hagenacker et al, 2010 ; Sun et al, 2018 ; Jang et al, 2020 ) may mediate the neuroprotective actions of myricetin. On the basis of these reports, we conclude that myricetin, dependent on its metabolites which possess neuroprotective activities, could be developed as a potential candidate for the treatment of nervous system disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The above data on the possible prominent role of brain ischemia in the induction of Alzheimer-type dementia may open up new innovative (probably preventive) treatments of AD with candidate drugs. One such candidate might be myricetin (a polyphenol) [ 186 ], whose beneficial characteristics seem perfectly tailored in this aim. As a matter of fact, myricetin reduces Aβ and amyloid oligomers/fibrils production, diminishes neuroinflammation, expresses powerful antioxidant activity and elevates brain acetylcholine level.…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo study using murine models of sepsis induced by lipopolysaccharides (LPS) and alum-induced peritonitis showed that myricetin inhibits the formation of the NLRP3 inflammasome [ 108 ]. Moreover, due to the pleiotropic properties of myricetin (anti-inflammatory, antioxidant, autophagous, and reduction of the formation of amyloid plaques and tau protein phosphorylation), myricetin is a promising compound for the treatment of neurodegeneration of the brain caused by ischaemia and full-blown dementia [ 109 ].…”
Section: Food Components With Regard To Their Protective Effects In Covid-19 Patientsmentioning
confidence: 99%